Migration from Ukraine: Brawn or Brain? New Survey Evidence - Simon Commander; Olexandr Nikolaychuk; Dmytro Vikhrov (Institute for the Study of Labor (IZA), 2013)
We study selection and labour market outcomes among Ukrainian migrants using unique data from a survey conducted in Ukraine in August - October 2011. We find that migrants are positively selected in terms of age and education. Yet, this is not associated, as might be expected, with their labour market outcomes. Notably, around half of the migrants are employed in occupations for which they are over-qualified. We conjecture that this downshifting in occupation can partly be explained by the absence of the conventional link between education and skills in Ukraine. To circumvent this problem, we compare pre- and post-migration labour market outcomes and find that the probability of downshifting decreases with the duration of stay in a foreign country and knowledge of the local language or English. Significantly, someone who downshifted prior to migration in the home country was more likely to downshift abroad. Further, we find that migrants to the EU are more likely to downshift when compared to other destinations.
Keywords: F22; J24; 330; migration; selection; occupation downshift; survey data